The effect of the project-based learning model on the ability to think creatively and interest in studying social studies at SDN 55 Pamanjengan, Moncongloe District, Maros Regency - Asriany Asran; Nursalam Nursalam; Syarifuddin Cn Sida (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this study was to collect, process, and present accurate data or information on the significant effect of applying the project based learning model in social studies learning on the creative thinking skills of students at SDN 55 Pamanjengan, Moncongloe Village, Moncongloe District, Maros Regency; and the significant effect of applying the project based learning learning model in social studies learning on students' social studies learning interest. This type of research is survey research with quasi-experimental techniques. The research population was all students of SDN 55 Pamanjengan, Moncongloe District, Maros Regency after the 2021/2022 school year with a total of 321 people with a sampling technique of 54 people according to the characteristics of experimental research using an experimental class and a control class. The results showed that the probability value of planting the concept (pretest-posttest experimental group) was 0.000 <0.05. The probability value of social studies interest (pretest-posttest experimental group) is 0.000 <0.05. The probability value of planting the concept (posttest control-experiment group) is 0.05 = 0.05. The probability value of interest in learning social studies (posttest control-experiment group) is 0.000 <0.05. so it can be understood that H0 in hypothesis 1 is rejected then Ho is rejected H1 is accepted. Likewise, H0 in hypothesis 2 is rejected, then Ho is rejected, H1 is accepted. Therefore, it can be stated that there is an influence of project-based learning (PBP) on the ability to think creatively in students of SDN 55 Pamanjengan, Moncongloe Village, Moncongloe District, Maros Regency. In addition, there is also the effect of project-based learning (PBP) on the interest in learning social studies students at SDN 55 Pamanjengan, Moncongloe Village, Moncongloe District, Maros Regency